Does Copper Contamination Affect Soil CO2 Emissions? A Literature Review - Sereni, Laura; Guenet, Bertrand; Lamy, Isabelle (Frontiers in Environmental Science, 2021)
Contaminated soils are widespread and contamination is known to impact several biotic soil processes. But it is still not clear to what extend soil contamination affects soil carbon efflux (CO2) occurring through soil microfauna respiration. Regarding the large stocks of organic carbon (C) stored in soils, even limited changes in the outputs fluxes may modify atmospheric CO2 concentration with important feedbacks on climate. In this study, we aimed at assessing and quantifying how soil respiration is affected by contamination. For that, we performed a quantitative review of literature focusing on i) soil heterotrophic respiration measurements thus excluding autotrophic respiration from plants, ii) soil copper contamination, and iii) the influence of pedo-climatic parameters such as pH, clay content or the type of climate. Using a dataset of 389 data analyzed with RandomForest and linear mixed statistical models, we showed a decrease in soil CO2 emission with an increase in soil copper contamination. Specific data from ex-situ spiking experiments could be easily differentiated from the ones originated from in-situ contamination due to their sharper decrease in soil organic carbon mineralization. Interestingly, ex-situ spikes data provided a threshold in soil Cu contents for CO2 emissions: CO2 emission increased for inputs below 265 mgCu.kg-1 soil and decreased above this concentration. Data from long-term in-situ contaminations due to anthropogenic activities (industrialization, agriculture, …) also displayed an impact on soil carbon mineralization, much particularly for industrial contaminations (smelter, sewage sludge, …) with decreased in CO2 emissions when Cu contamination increased. Soil pH was identified as a significant driver of the effect of Cu on CO2 emissions, as soil C mineralization was found more sensitive to Cu contamination in acidic soils than in neutral or alkaline soils. Conversely the clay content and the type of climate did not significantly explain the responses in soil C mineralization. Finally, the collected data were used to propose an empirical equation quantifying how soil respiration can be affected by a Cu contamination.